Characteristic of compressive and tensile strength using the organic cement compare with portland cement. (December 2018) - Syarif, Muhammad; Sampebulu', Victor; Wihardi Tjaronge, M.; Nasruddin,
Abstract: The waste problem is a problem faced throughout the world. This research aims to save the environment with on the utilization of recycling waste materials that do not contribute much in people's lives over the years. Organic cement is an alternative cement besides portland cement made from organic waste recyled and substitution of mediteran soil. The research is oriented to chemical compounds, compressive strength, and tensile strength testings of concrete by using organic and portland cements. Age of concrete in the research are 3, 4, 14, 21, and 28 days old. Result for compressive test of cylinder concrete with organic cement, it obtained 6.10 MPa while the cylincer concrete with portland cement, it obtained 20.22 MPa. For tensile strength test of cylinder concrete with organic cement on 28-days-old concrete reached 1.09 MPa and those with portland cement reached 2.01 MPa. From the physical test result, it obtained the density of organic cement is 3.01 g/ml, while for the density of portland cement is 3.16 g/ml. From the analysis of organic cement chemical compounds through laboratory testing methods result, it found indications that resemble portland cement chemical compounds that are CaO;65, 36%, SiO₂; 18, 84%, Al₂O₃; 6, 33%, Fe₂O₃; 2, 29%, SO₃ ; 3, 64%, MgO; 1, 35%, C₃S; 66, 72%, C₂S; 3, 98%, C₃A; 12, 9%, and C4Af; 6, 97%.